Beyond Participation: the Practical Application of an Empowerment Process to Bring about Environmental and Social Change - Mathers, Alice R.; Thwaites, Kevin; Simkins, Ian M.; Mallett, Rebecca (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change)

(untitled) (Réseau International sur le Processus de Production du Handicap, 2011)
The ability to communicate empowers individuals, enabling them to share information, needs and experiences with others (Cockerill, 2002). For many, society’s general reliance upon verbal and written communication is taken for granted. However for the vulnerable minority, including people with learning disabilities (PWLD), this is a key issue. Physiological, psychological, environmental and social barriers make traditional methods of communication extremely frustrating or impossible, continuing their legacy of exclusion from decision-making society. Moreover, whilst the Habermas ideal of a society where “communication will no longer be distorted by the effects of power, self-interest or ignorance” (Tewdwr-Jones & Allmendinger, 1998 citing Norris, 1985, p. 149) propels the acceptance of communicative rationality in policy and practice (Healey, 1999), there is limited evidence regarding its practical employment to extend inclusion to underrepresented groups such as PWLD. In order to address this evident lack in employment of participatory processes that value difference, the Experiemic process was developed as part of a two year research program funded by the UK Leverhulme Trust. Through its employment, it is seen how we can facilitate more inclusive partnerships that have the capability to augment and challenge current consultation techniques. We illustrate this through a longitudinal qualitative fieldwork study into a United Kingdom (UK) city’s local public transport system. Here, the Experiemic process’s catalytic capability is revealed in its ability to empower and facilitate PWLD. As a consequence the learning disability participants evolve as key players in environmental decision-making, whilst partnerships developed across academia, the community, practice and policy result in positive environmental and social change.